Burnout Syndrome Amongst Medicine Students in Lithuania and Germany - Rudinskaitė, Ieva; Mačiūtė, Eglė; Gudžiūnaitė, Giedrė; Gerulaitytė, Greta (Acta medica Lituanica, 2024)
Background. The research provides comparative analysis of the burnout syndrome among medical students in Lithuania and Germany and determines relations between burnout and lifestyle, health complaints and seeking for psychological help. Materials and methods. The research was conducted in April 2019 using an anonymous self-administered e-based questionnaire. The sample size was 261 medical students (age mean 20,5 ± 1,8, 46 males, 215 females): 131 from Vilnius University (VU), 67 from Lithuanian University of Health Science (LSMU) and 63 from Heidelberg University (HU), Germany. The 15 items MBI-SS scale was used to identify burnout syndrome among students (Cronbach α =0,74). Emotional exhaustion (>14), cynicism (>6), and professional efficacy (<23) scores were calculated for academic burnout. The participants were also asked additional questions related to lifestyle and well-being. Descriptive statistics were analysed using MS Office Excel, SPSS and R Commander, results were statistically significant when p<0,05. Results. 51 (38,9%) VU, 25 (37,3%) LSMU and 10 (15,9%) HU students were ascertained as burnt-out (p=0,004). 76 (90,6%) respondents complained of feeling study induced mental stress (p=0,0002). Furthermore, 67 (77,9%) respondents indicated having a bad mood (p=0,043), 54 (62,7%) general weakness (p=0,024), 44 (51,1%) digestive problems (p=0,003). Sleep duration was strongly associated with burnout (p=0,002) with over half (n=51, 59,3%) of the burnout respondents sleeping <7 hours a day. 87 (33,3%) students considered consulting a psychologist, but only 24 (9,2%) reached out for help. Conclusions. More than 1/3 of medical students in the research group had signs of burnout. The highest prevalence of burnout was among VU and lowest among HU students. Burnt-out respondents complained of mental stress, weakness, bad mood, digestive problems. The university studies and the duration of sleep can impact the occurrence of burnout syndrome. Only every forth student, willing to consult a psychologist, sought assistance.